Publishing Revolution: Publishing Praxis in the Classroom - Przybylo, Ela (Radical Teacher, 2019)
Drawing on queer and feminist Digital Humanities (DH) and Indigenous, antiracist, and intersectional approaches to publishing, this pedagogy piece reflects on a course designed and taught in Fall 2018 titled “Intersectional Feminist Journal Praxis.” Students read intersectional readings on publishing while creating their own journal through Open Journal Systems Software (OJS). Employing principles of collaboration and praxis, students worked in teams around specific tasks like a call for papers, peer review, copyediting, and introduction-writing while employing critical publishing practices such as remaining reflexive about, for example, accessibility and power inequalities in processes of knowledge production. Their end product was the publication of the first issue of the journal they themselves created by the name of Intersectional Apocalypse (https://journals.lib.sfu.ca/index.php/ifj). This piece discusses this pedagogical DH experiment, grounding it in histories of anti-oppressive publishing endeavors and in students’ own words and reflections on the course.